Caracterización físico-química del agua y su relación con el uso del suelo en el río teaone, cantones Esmeraldas, año 2019 - Ramírez Castillo, Andy Jafet (2021)
The objective of the research was to evaluate the influence of different land uses and landscape fragmentation on the physical-chemical characteristics of the water of the Teaone River, Esmeraldas province, Ecuador. The physical-chemical parameters were characterized under the influence of different land uses. The influence of landscape fragmentation on the physical-chemical parameters of the water was determined and an environmental education proposal was developed. Eight water samples were taken by land use (livestock, agroforestry systems, remnants of forests and urban areas). Temperature, turbidity, total dissolved solids (TDS), pH, electrical conductivity, dissolved oxygen (DO) and salinity were determined. Data on the type of vegetation, land use, geographic coordinates, altitude, flow width, river substrate, and water depth were recorded. Circular digital plots of 500 m in diameter were created, obtaining indicators of the structure of the habitats and their fragmentation. Variables derived from the edge index, dominance and fragmentation index were obtained. A spectral description was obtained through spectral indices (NDVI, enhanced vegetation index (EVI), near infrared NIR, red, blue). The average values were: turbidity = -38.7 (1.61 NTU), pH = 8.1, electrical conductivity = 365 μS / cm, dissolved oxygen = 4.04, temperature = 26.0 ºC, total dissolved solids = 186.1 (Mg / L), salinity = 0.15 g / L. The highest average value corresponded to the area of pastures 12.1, followed by the area of towns with 9.4, the lowest value of area corresponded to that of crops 1.7 and that of native forest 6.7. The same trend was observed for the red and blue index, the highest reflectance values were in urban use, different from the rest of the categories. For NIR, EVI and NDVI a contrary trend was observed, the highest values were identified in native forest, agroforestry and livestock and the lowest value in the urban area. It was concluded that the physical-chemical parameters turbidity, pH, electrical conductivity, temperature and salinity are within the permissible limits proposed by the national and international regulations consulted. The averages obtained in all land uses for dissolved oxygen, dissolved solids were outside the permissible limits. The physical-chemical parameters show that in agroforestry systems and native forests a good quality of water is maintained while in livestock and urban land uses its quality decreases. In the landscape, the high values of water temperature were associated with a smaller area of native forest and agroforestry area. Higher conductivity values are associated with a greater number of land uses, which implies greater fragmentation. Dissolved oxygen had positive associations with the agroforestry area, since higher dissolved oxygen values are associated with a larger agroforestry area. Dissolved solids were negatively correlated with native forest area. Keywords: Water quality, anthropogenic activities, fragmentation, landscape, spatial analysis